2017
DOI: 10.1139/cgj-2016-0403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NaCl on drying shrinkage behavior of low-plasticity soil in earthen heritages

Abstract: Cracking of wall surface crusts on salt-laden earthen remains at the site of Yar City, northwest China, is a serious concern. This widespread pathology is closely related to the drying shrinkage behavior of soil and the fundamental mechanisms should be investigated to better interpret the deterioration of these precious heritages. In this paper, tests were conducted on specimens that were initially slurries with NaCl contents of 0%, 2%, and 5%. The soil shrinkage characteristic curve (SSCC) was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 96 publications
3
7
0
Order By: Relevance
“…It appears that all the points lay on one unique line, suggesting that the matric suction was highly related to the water content of samples, whereas the salinity had no significant effect on matric suction. This was in good agreement with previous results from Miller and Nelson (1993), Leong et al (2007), Sreedeep and Singh (2011) and Zhang et al (2017). It was also observed that, for the dry samples with the same water content, the matric suctions of saltless and saline samples were quite close, while the matric suctions of saltless samples compacted at optimum state and on wet side were Fig.…”
Section: Matric Suctionsupporting
confidence: 92%
“…It appears that all the points lay on one unique line, suggesting that the matric suction was highly related to the water content of samples, whereas the salinity had no significant effect on matric suction. This was in good agreement with previous results from Miller and Nelson (1993), Leong et al (2007), Sreedeep and Singh (2011) and Zhang et al (2017). It was also observed that, for the dry samples with the same water content, the matric suctions of saltless and saline samples were quite close, while the matric suctions of saltless samples compacted at optimum state and on wet side were Fig.…”
Section: Matric Suctionsupporting
confidence: 92%
“…The changes of intermolecular interactions and porosity are expected to influence s M . However, such the dependence on concentration and porosity is much weaker compared to the dependence on water content (Zhang et al, ) and will be neglected in the following derivations. That is to say, once we obtain the s M ‐ w relationship in the condition of c = 0 and p i = 0, we can apply this s M ‐ w relationship to the cases with variable c and p i , as will be shown in section .…”
Section: A Generalized Clapeyron Equationmentioning
confidence: 99%
“…A third mode corresponded to a bi-modal PSD where drying resulted in a reduction of macro-pore (or inter-aggregate pore) volume and thus an increase of micro-pore (or intra-aggregate pore) volume in which the macro-pores and micro-pores were delimitated at entrance pore diameter of 0.22 μm. Zhang et al (2017) conducted MIP tests on dried low plasticity soil slurries and reported that the uni-modal PSD curves first experienced a shift of the peak pore modal size to a lower value without much reduction of magnitude. But with further drying, the uni-modal PSD curves changed to a bimodal pattern.…”
Section: Introductionmentioning
confidence: 99%